Does 2000-m rowing ergometer performance time correlate with final rankings at the World Junior Rowing Championship? A case study of 398 elite junior rowers - Mikuli, P.; Smoljanovi, T.; Bojani, I.; Hannafin, J.; Pedisic, Z. (Journal of Sports Sciences, 2009)
In this study, we assessed the extent to which 2000-m rowing ergometer performance predicted final rankings at the World Junior Rowing Championship in a sample of 398 junior rowers competing in 13 events. The rowers' ergometer performance times were examined using a questionnaire, and in all 13 events they correlated (P = 0.039) with the final rankings at the Championship. The strongest correlations were observed for ergometer performance times in junior women's single sculls (r = 0.92; P < 0.001), followed by junior men's single sculls (r = 0.80; P < 0.001) and junior women's double sculls (r = 0.79; P < 0.001). The observed correlations were higher for smaller boats - singles, doubles, and pairs (r = 0.64-0.92; P = 0.025) - than for larger boats - quads, fours, and eights (r = 0.31-0.70; P = 0.039). Linear regression analyses were used to construct regression equations to predict final rankings based on 2000-m rowing ergometer performance times for each event. Although correlations in 10 of the 13 events were above r = 0.5, the large standard errors of the estimate impaired the prediction of rankings in all of the studied events. Using these equations, the most probable rowing ergometer performance times required for a particular ranking in a given rowing event might easily be calculated.